Entrepreneurial Cognition Exploring the Mindset of Entrepreneurs - Shepherd, Dean A. (Springer International Publishing, 2018)
This open access book investigates the inter-relationship between the mind and a potential opportunity to explore the psychology of entrepreneurship. Building on recent research, this book offers a broad scope investigation of the different aspects of what goes on in the mind of the (potential) entrepreneur as he or she considers the pursuit of a potential opportunity, the creation of a new organization, and/or the selection of an entrepreneurial career. This book focuses on individuals as the level of analysis and explores the impact of the organization and the environment only inasmuch as they impact the individual's cognitions. Readers will learn why some individuals and managers are able to able to identify and successfully act upon opportunities in uncertain environments while others are not. This book applies a cognitive lens to understand individuals' knowledge, motivation, attention, identity, and emotions in the entrepreneurial process. .